Penguatan Moderasi Beragama di Madura melalui Jejaring Sosial Keagamaan Pesantren - Abd Hannan (Fakultas Ushuluddin, Adab dan Humaniora (FUAH) UIN Kiai Haji Achmad Siddiq Jember, 2022)
Abstract: This study examines the strengthening of religious moderation in Madura through religious social networks of pesantren. There are two research questions discussed in this study, how are the dynamics of religious moderation in Madura? How to strengthen religious moderation in Madura through pesantren religious social networks? This study is a literature review that uses qualitative research. Sources and types of data in this study are secondary data, especially data from the literature. By analyzing based on the perspective of social networking theory from John Arundel Barnes, this study finds that in the culture of the Madurese community, pesantren is an institution of da'wah and religious education that has a major role and influence in shaping the religious reality of the community. The magnitude of the influence of the pesantren is clearly reflected in the Islamic patterns and behavior of the Madurese community who always make the pesantren a religious reference, both in thought and ritual. In terms of strengthening religious moderation in Madura, pesantren has a strategic role and function. Apart from having a high social position, Islamic boarding schools also have quite strong tools and social capital. The social capital is in their religious social network which is widespread throughout the Madura area. The concept of social networking here refers to the main elements in the religious structure of pesantren. The main elements include Kiai, santri, and finally Islamic organizations, in this case, the Nahdatul Ulama (NU) organization.